Raw material circulation at broad scales in southern Patagonia (Argentina): The cases of the Chico and Santa Cruz River basins - Franco, Nora Viviana (2015)
The purpose of this paper is to begin to understand human mobility through rock transport at different times in two areas with different environmental characteristics: the Southern Deseado Massif and the basaltic canyons north of the Santa Cruz River. We focus on obsidian, which has a clear geochemical signature and an uneven distribution. Additionally, we use macroscopic information on siliceous rocks, which at present have only been identified in northern areas, although they may also be recovered randomly and in low frequencies in southern ones.During the initial peopling of the Southern Deseado Massif (ca. 10,800BP), inhabitants were transporting black obsidian as well as translucent chalcedony, probably as part of the individual gear. During the Late Holocene, the number of obsidian artifacts decreased in the Southern Deseado Massif, related to a better knowledge of the high-quality local lithic resources and/or to the existence of higher population densities. Obsidian artifacts are more abundant in the northern Santa Cruz River basin than in the southern Deseado Massif, suggesting the existence of a relationship with areas located to the northwest, close to the obsidian source, as other lines of evidence suggest. In addition, the presence in the basaltic canyons of artifacts made from high-quality siliceous rocks, more abundant and predictable in northern areas, could also be the result of human movements following a north-south direction.